A readily rinsed styling wax and method of making same
Patent Information
- Application Number
- CN202611266896.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-30
AI Technical Summary
然而,上述方式均存在各自的局限性
[0027](1)本发明以聚丙烯酸钠接枝淀粉作为吸水响应主体,并在其颗粒表面复合PEG-100硬脂酸酯、甘油硬脂酸酯和微晶蜡,形成能够分散于疏水性油蜡基质中的复合微粒。通过颗粒表面的复合结构改善聚丙烯酸钠接枝淀粉与油蜡基质之间的界面相容性,使复合微粒能够嵌入由蜡质材料和油性组分构成的定型层中,而非以与定型基质相对独立的吸水粉体形式存在,为洗涤过程中复合微粒与周围定型材料之间的协同脱除提供基础。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hair wax technology, and relates to an easy-to-wash styling hair wax and its preparation method. Background Technology
[0002] Hair wax is a commonly used hair styling product. It typically forms a styling layer with a certain mechanical strength and adhesion on the hair surface through waxy materials, oily components, and film-forming styling materials, thereby giving the hair shaping, texture retention, and style fixation. To improve the styling strength and durability of hair wax, existing products usually use a certain amount of hydrophobic waxy materials, oily components, or water-resistant film-forming materials.
[0003] However, while the aforementioned hydrophobic components improve styling performance, they also create a hydrophobic film on the hair surface that is difficult to wet and disperse with water. Especially when the content of wax and film-forming materials is high, the styling substance tends to adhere to the hair surface and is not easily emulsified and removed during regular shampooing, which may lead to problems such as increased washing frequency, hair residue, stickiness after washing, or decreased combability.
[0004] To improve the cleansing performance of styling products, existing technologies typically employ the following approaches: first, reducing the content of waxes or hydrophobic film-forming materials; second, increasing the proportion of hydrophilic components in the formulation; and third, adding surfactants to promote emulsification. However, each of these methods has its limitations. Reducing the content of hydrophobic styling components weakens the product's support and style retention; increasing the hydrophilicity of the system may cause the styling film to soften prematurely in sweat or high humidity environments, reducing style durability; and higher amounts of surfactants may affect the wax's texture, application smoothness, and the feel of the hair after use.
[0005] Therefore, how to ensure that the styling layer can be quickly removed during shampooing and reduce hair residue while maintaining the basic styling function of hair wax is a technical problem that existing hair wax products still need to solve. Summary of the Invention
[0006] The purpose of this invention is to provide an easy-to-wash hair wax and its preparation method. By introducing composite microparticles, the hair wax's styling performance is maintained while its washability is improved.
[0007] The objective of this invention can be achieved through the following technical solutions:
[0008] In a first aspect, the present invention provides an easy-to-wash styling wax comprising the following raw materials: microcrystalline wax, candelilla wax, ceresin wax, hydrogenated polyisobutylene, C12-15 benzoyl alcohol, caprylic / capric triglyceride, composite microparticles, PEG-40 hydrogenated castor oil, polyglycerol-10 laurate, and a structure modifier.
[0009] The composite microparticles are composed of sodium polyacrylate grafted starch, PEG-100 stearate, glyceryl stearate and microcrystalline wax, wherein the PEG-100 stearate, glyceryl stearate and microcrystalline wax are loaded on the surface of the sodium polyacrylate grafted starch particles.
[0010] This invention uses sodium polyacrylate grafted starch as the water-responsive component of composite microparticles, and further composites PEG-100 stearate, glyceryl stearate, and microcrystalline wax onto the particle surface. Glyceryl stearate and microcrystalline wax enhance the interfacial compatibility between the composite microparticles and the hair wax matrix, allowing the composite microparticles to disperse within a hydrophobic styling matrix. PEG-100 stearate, with its hydrophilic polyoxyethylene segments, facilitates the wetting of the composite microparticle interface by water and the washing medium during washing. Thus, the composite microparticles achieve both dispersion stability in the wax matrix and water responsiveness during washing.
[0011] Preferably, the mass ratio of sodium polyacrylate grafted starch, PEG-100 stearate, glyceryl stearate and microcrystalline wax in the composite microparticles is (85-90):(4-6):(4-6):(1-3).
[0012] By adopting the above mass ratio, on the one hand, the proportion of sodium polyacrylate grafted starch in the composite microparticles can be maintained at a high level, thereby ensuring that the composite microparticles have sufficient water absorption response capacity; on the other hand, PEG-100 stearate, glyceryl stearate and microcrystalline wax can form an appropriate amount of interface modification components on the surface of sodium polyacrylate grafted starch particles, which improves the compatibility between the composite microparticles and the oil and wax matrix, while avoiding excessive obstruction of water transfer to the interior of sodium polyacrylate grafted starch during the washing process due to excessive amount of surface hydrophobic components.
[0013] Preferably, the average particle size of the sodium polyacrylate grafted starch is 10-30 μm.
[0014] Preferably, the method for preparing the composite microparticles is as follows: PEG-100 stearate, glyceryl stearate and microcrystalline wax are mixed and heated to form a melt, the resulting melt is added to sodium polyacrylate grafted starch and mixed, so that the melt adheres to the surface of the sodium polyacrylate grafted starch particles, and then cooled, solidified, depolymerized and sieved to obtain the composite microparticles.
[0015] Preferably, the sieving step is as follows: sieving is performed using a sieve with a mesh size of 50-75μm.
[0016] The 10-30 μm range specified in this invention refers to the average particle size of the sodium polyacrylate grafted starch raw material used to prepare the composite microparticles, not the final particle size of the composite microparticles. During the composite process of sodium polyacrylate grafted starch and the melt, some particles may agglomerate to a certain extent due to the PEG-100 stearate, glyceryl stearate, and microcrystalline wax adhering to their surfaces. Therefore, deagglomeration and sieving are performed after cooling and solidification. Using a sieve with a mesh size of 50-75 μm can remove larger agglomerates formed during the composite process, while avoiding excessive pulverization of the sodium polyacrylate grafted starch main particles, which is beneficial for obtaining composite microparticles with better dispersibility.
[0017] Preferably, the raw materials include the following parts by weight: 12-16 parts microcrystalline wax, 5-7 parts candelilla wax, 4-6 parts ceresin wax, 31-36 parts hydrogenated polyisobutylene, 16-20 parts C12-15 benzoyl alcohol, 10-13 parts caprylic / capric triglyceride, 2.5-3.5 parts composite microparticles, 3.5-4.5 parts PEG-40 hydrogenated castor oil, 1.5-2.5 parts polyglycerol-10 laurate, and 1.0-2.0 parts structure modifier.
[0018] Preferably, the structure modifier is hydrophobic fumed silica.
[0019] Preferably, it also includes the following raw materials in parts by weight: 0.2-0.4 parts of tocopherol and 0-0.3 parts of fragrance.
[0020] In a second aspect, the present invention provides a method for preparing an easy-to-wash styling wax as described in the first aspect, comprising the following steps:
[0021] S1. Mix microcrystalline wax, candelilla wax, ceresin, hydrogenated polyisobutylene, C12-15 alcohol benzoate and caprylic / capric triglyceride and heat to 80-85℃ to melt the wax components and obtain the oil wax matrix.
[0022] S2. Add PEG-40 hydrogenated castor oil and polyglycerol-10 laurate to the oil and wax matrix, mix evenly, then add a structure modifier and disperse evenly to obtain the hair wax matrix;
[0023] S3. After cooling the hair wax base to 60-65℃, add the composite microparticles and stir to make the composite microparticles evenly dispersed in the hair wax base;
[0024] S4. Fill at 45-50℃, cool and solidify, and let stand to obtain the easy-to-clean hair wax.
[0025] Preferably, in step S1, the heating and melting temperature of microcrystalline wax, candelilla wax, and ceresin wax is 80-85℃, and the stirring time is 15-20 min; in step S3, after cooling to 60-65℃, composite microparticles are added, and the stirring time is 5-10 min.
[0026] The beneficial effects of this invention are:
[0027] (1) This invention uses sodium polyacrylate grafted starch as the water-absorbing response host, and composites PEG-100 stearate, glyceryl stearate and microcrystalline wax on its particle surface to form composite microparticles that can be dispersed in a hydrophobic oil and wax matrix. The composite structure on the particle surface improves the interfacial compatibility between sodium polyacrylate grafted starch and the oil and wax matrix, so that the composite microparticles can be embedded in the shaping layer composed of waxy materials and oily components, rather than existing as water-absorbing powders that are relatively independent of the shaping matrix, thus providing a basis for the synergistic removal of the composite microparticles and the surrounding shaping materials during the washing process.
[0028] (2) During the shampooing process, the liquid water and surfactants in the shampoo wet the styling layer and gradually enter the area where the composite microparticles are located. PEG-100 stearate is beneficial to the wetting of the interface of the composite microparticles by the washing medium, which causes the sodium polyacrylate grafted starch to absorb water and undergo volume change. Since the composite microparticles are embedded in the oil and wax styling layer, their water absorption volume change can cause local structural disturbance to the surrounding wax and oily styling materials, causing the styling layer that was originally continuous and attached to the hair surface to loosen, crack locally and become unstable at the interface, which is conducive to the washing medium further penetrating into the interior of the styling layer. As the washing process continues, the composite microparticles that undergo hydration and volume changes work synergistically to remove the loosened wax and oily styling components around them. Under the wetting, emulsification, and mechanical shearing action of the washing medium, the composite microparticles, while undergoing interfacial detachment and dispersion, can promote the detachment of adjacent wax and oily styling materials from the hair surface. This transforms the originally continuously attached styling residue into particles or aggregates that are more easily dispersed and carried away by the washing medium, thereby reducing the residue of wax and oily components on the hair surface and improving the washing efficiency of hair wax.
[0029] (3) This invention combines the washing response of the composite microparticles with the wetting and dispersing effects of PEG-40 hydrogenated castor oil and polyglycerol-10 laurate, so that the easy-to-wash performance is not mainly achieved by reducing the amount of wax-based styling material or significantly increasing the overall hydrophilicity of the system. Therefore, while retaining the oil-wax styling system composed of microcrystalline wax, candelilla wax and ceresin wax, it can balance the styling performance and washing and removal performance of hair wax. Detailed Implementation
[0030] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with embodiments, is provided below.
[0031] The following descriptions of some of the raw materials used in the examples and comparative examples are as follows:
[0032] Sodium polyacrylate grafted starch was derived from the commercially available product MAKIMOUSSE 25, with an average particle size of 25 μm;
[0033] PEG-100 stearate is sourced from Haian County Guoli Chemical Co., Ltd., cosmetic grade, SG-100, CAS No.: 9004-99-3, cosmetic grade;
[0034] Glyceryl stearate is derived from Lexemul® 515 MB from Inolex, CAS No.: 85666-92-8;
[0035] Microcrystalline wax is sourced from Microfumei Biotechnology Co., Ltd. ® 6302;
[0036] PEG-40 hydrogenated castor oil is sourced from BASF's EUMULGIN plant in Germany. ® CO 40;
[0037] Polyglycerol-10 laurate is sourced from Shandong Binzhou Jinsheng New Material Technology Co., Ltd., CAS No.: 34406-66-1, cosmetic grade;
[0038] The structure modifier is hydrophobic fumed silica, derived from Evonik's AEROSIL in Germany. ® R972;
[0039] Candelilla wax, CAS No.: 8006-44-8, cosmetic grade;
[0040] Ceresin, CAS No.: 8001-75-0, cosmetic grade;
[0041] Hydrogenated polyisobutylene, CAS No.: 68937-10-0, cosmetic grade;
[0042] C12-15 alcohol benzoate, CAS No.: 68411-27-8, cosmetic grade;
[0043] Caprylic / capric triglyceride, CAS No.: 65381-09-1, cosmetic grade;
[0044] Except for the ingredients explicitly mentioned above, all other ingredients not specifically mentioned are conventional cosmetic-grade products and can be easily obtained through commercial channels.
[0045] Example 1
[0046] An easy-to-wash styling wax comprises the following raw materials in parts by weight: 14 parts microcrystalline wax, 6 parts candelilla wax, 5 parts ceresin wax, 34 parts hydrogenated polyisobutylene, 18 parts C12-15 benzoyl alcohol, 11 parts caprylic / capric triglyceride, 3 parts composite microparticles, 4 parts PEG-40 hydrogenated castor oil, 2 parts polyglycerol-10 laurate, 1.5 parts hydrophobic fumed silica, 0.3 parts tocopherol, and 0.2 parts fragrance.
[0047] The composite microparticles include the following raw materials in parts by weight: 88 parts of sodium polyacrylate grafted starch (average particle size 25μm), 5 parts of PEG-100 stearate, 5 parts of glyceryl stearate, and 2 parts of microcrystalline wax.
[0048] The method for preparing composite microparticles includes the following steps:
[0049] A1. Place 88 parts of sodium polyacrylate grafted starch in a forced-air drying oven and dry at 48℃ for 1.5h. After removing it, seal it and cool it to 30℃ for later use.
[0050] A2. Mix 5 parts PEG-100 stearate, 5 parts glyceryl stearate and 2 parts microcrystalline wax, heat to 82°C and stir at 400 rpm; after the components form a uniform melt, continue stirring for 5 minutes to obtain the melt.
[0051] A3. Add the sodium polyacrylate grafted starch obtained in step A1 to a high-speed mixer and start stirring at 1000 rpm to keep the powder in a continuous flow state. While stirring continuously, add the melt obtained in step A2 slowly dropwise, controlling the powder temperature to not exceed 60℃. The melt addition time is 8 minutes, and the mixing speed is 1500 rpm during the addition process.
[0052] A4. After all the melt has been added, continue mixing at 800 rpm for 8 minutes, then stop heating and continue stirring at 500 rpm to cool the material. After the material temperature drops to 38°C, continue mixing for 8 minutes, then stop stirring and cool to room temperature.
[0053] A5. After cooling, the material is deagglomerated at 800 rpm for 2 minutes, and then sieved using a 60 μm sieve. The material passing through the sieve is collected to obtain composite microparticles.
[0054] A method for preparing an easy-to-wash styling wax includes the following steps:
[0055] S1. Mix 14 parts microcrystalline wax, 6 parts candelilla wax, 5 parts ceresin wax, 34 parts hydrogenated polyisobutylene, 18 parts C12-15 alcohol benzoate and 11 parts caprylic / capric triglyceride, heat to 82°C, and stir at 400 rpm for 16 minutes to melt the wax components and mix them evenly with the oil components to obtain an oil-wax matrix.
[0056] S2. Keep the system temperature at 78℃, add 4 parts of PEG-40 hydrogenated castor oil and 2 parts of polyglycerol-10 laurate, stir at 500 rpm for 10 min to evenly disperse it in the oil and wax matrix; then slowly add 1.5 parts of hydrophobic fumed silica, increase the shear rate to 1200 rpm, disperse for 10 min to obtain the hair wax matrix.
[0057] S3. Cool the hair wax base to 62℃, add 3 parts of composite microparticles, and stir at 500 rpm for 8 minutes to evenly disperse the composite microparticles in the hair wax base.
[0058] S4. Cool the system to 55°C, add 0.3 parts tocopherol and 0.2 parts fragrance, stir at 400 rpm for 5 minutes to mix evenly; continue to cool to 48°C, fill the wax while it is still fluid, let it cool naturally to room temperature, and then let it stand at 25°C for 24 hours to obtain an easy-to-wash styling wax.
[0059] Example 2
[0060] An easy-to-wash styling wax comprises the following raw materials in parts by weight: 12 parts microcrystalline wax, 5 parts candelilla wax, 4 parts cerescargot, 31 parts hydrogenated polyisobutylene, 16 parts C12-15 benzoyl alcohol, 10 parts caprylic / capric triglyceride, 2.5 parts composite microparticles, 3.5 parts PEG-40 hydrogenated castor oil, 1.5 parts polyglycerol-10 laurate, 1.0 part hydrophobic fumed silica, 0.2 parts tocopherol, and 0.1 parts fragrance.
[0061] The composite microparticles include the following raw materials in parts by weight: 85 parts of sodium polyacrylate grafted starch (average particle size 25μm), 4 parts of PEG-100 stearate, 4 parts of glyceryl stearate, and 1 part of microcrystalline wax.
[0062] The method for preparing composite microparticles includes the following steps:
[0063] A1. Place 85 parts of sodium polyacrylate grafted starch in a forced-air drying oven and dry at 45°C for 2 hours. After removing it, cool it in a sealed container to 25°C for later use.
[0064] A2. Mix 4 parts of PEG-100 stearate, 4 parts of glyceryl stearate and 1 part of microcrystalline wax, heat to 80°C and stir at 350 rpm; after the components form a uniform melt, continue stirring for 6 minutes to obtain the melt.
[0065] A3. Add the sodium polyacrylate grafted starch obtained in step A1 to a high-speed mixer and start stirring at 800 rpm to keep the powder in a continuous flow state. While stirring continuously, add the melt obtained in step A2 slowly dropwise, controlling the powder temperature to not exceed 55℃. The melt addition time is 10 minutes, and the mixing speed is 1200 rpm during the addition process.
[0066] A4. After all the melt has been added, continue mixing at 600 rpm for 10 minutes, then stop heating and continue stirring at 400 rpm to cool the material. After the material temperature drops to 35°C, continue mixing for 10 minutes, then stop stirring and cool to room temperature.
[0067] A5. After cooling, the material is deagglomerated at 600 rpm for 3 minutes, and then sieved using a sieve with a mesh size of 50 μm. The material passing through the sieve is collected to obtain composite microparticles.
[0068] A method for preparing an easy-to-wash styling wax includes the following steps:
[0069] S1. Mix 12 parts microcrystalline wax, 5 parts candelilla wax, 4 parts cerescarpone, 31 parts hydrogenated polyisobutylene, 16 parts C12-15 alcohol benzoate and 10 parts caprylic / capric triglyceride, heat to 80°C, and stir at 350 rpm for 20 minutes to melt the wax components and mix them evenly with the oil components to obtain an oil-wax matrix.
[0070] S2. Keep the system temperature at 75℃, add 3.5 parts of PEG-40 hydrogenated castor oil and 1.5 parts of polyglycerol-10 laurate, stir at 400 rpm for 12 min to evenly disperse it in the oil and wax matrix; then slowly add 1.0 part of hydrophobic fumed silica, increase the shear rate to 1000 rpm, disperse for 15 min to obtain the hair wax matrix;
[0071] S3. Cool the hair wax base to 60℃, add 2.5 parts of composite microparticles, and stir at 400 rpm for 10 minutes to ensure that the composite microparticles are evenly dispersed in the hair wax base.
[0072] S4. Cool the system to 52°C, add 0.2 parts tocopherol and 0.1 parts fragrance, stir at 350 rpm for 5 minutes to mix evenly; continue to cool to 45°C, fill the wax while it is still fluid, let it cool naturally to room temperature, and then let it stand at 22°C for 48 hours to obtain an easy-to-wash styling wax.
[0073] Example 3
[0074] An easy-to-wash styling wax comprises the following raw materials in parts by weight: 16 parts microcrystalline wax, 7 parts candelilla wax, 6 parts cerescargot, 36 parts hydrogenated polyisobutylene, 20 parts C12-15 benzoyl alcohol, 13 parts caprylic / capric triglyceride, 3.5 parts composite microparticles, 4.5 parts PEG-40 hydrogenated castor oil, 2.5 parts polyglycerol-10 laurate, 2.0 parts hydrophobic fumed silica, 0.4 parts tocopherol, and 0.2 parts fragrance.
[0075] The composite microparticles include the following raw materials in parts by weight: 90 parts of sodium polyacrylate grafted starch (average particle size 25μm), 6 parts of PEG-100 stearate, 6 parts of glyceryl stearate, and 3 parts of microcrystalline wax.
[0076] The method for preparing composite microparticles includes the following steps:
[0077] A1. Place 90 parts of sodium polyacrylate grafted starch in a forced-air drying oven and dry at 50°C for 1 hour. After removing it, seal it and cool it to 35°C for later use.
[0078] A2. Mix 6 parts PEG-100 stearate, 6 parts glyceryl stearate and 3 parts microcrystalline wax, heat to 85°C and stir at 500 rpm; after the components form a uniform melt, continue stirring for 5 minutes to obtain the melt.
[0079] A3. Add the sodium polyacrylate grafted starch obtained in step A1 to a high-speed mixer and start stirring at 1200 rpm to keep the powder in a continuous flow state. While stirring continuously, add the melt obtained in step A2 slowly dropwise, controlling the powder temperature to not exceed 60℃. The melt addition time is 5 minutes, and the mixing speed is 1800 rpm during the addition process.
[0080] A4. After all the melt has been added, continue mixing at 1000 rpm for 5 minutes, then stop heating and continue stirring at 600 rpm to cool the material. After the material temperature drops to 40°C, continue mixing for 5 minutes, then stop stirring and cool to room temperature.
[0081] A5. After cooling, the material is deagglomerated at 1000 rpm for 1 minute, and then sieved using a sieve with a mesh size of 75 μm. The material passing through the sieve is collected to obtain composite microparticles.
[0082] A method for preparing an easy-to-wash styling wax includes the following steps:
[0083] S1. Mix 16 parts microcrystalline wax, 7 parts candelilla wax, 6 parts cerescarpone, 36 parts hydrogenated polyisobutylene, 20 parts C12-15 alcohol benzoate and 13 parts caprylic / capric triglyceride, heat to 85°C, and stir at 500 rpm for 15 minutes to melt the wax components and mix them evenly with the oil components to obtain an oil-wax matrix.
[0084] S2. Keep the system temperature at 80℃, add 4.5 parts of PEG-40 hydrogenated castor oil and 2.5 parts of polyglycerol-10 laurate, stir at 600 rpm for 8 min to evenly disperse it in the oil and wax matrix; then slowly add 2.0 parts of hydrophobic fumed silica, increase the shear rate to 1500 rpm, disperse for 8 min to obtain the hair wax matrix;
[0085] S3. Cool the hair wax base to 65°C, add 3.5 parts of composite microparticles, and stir at 700 rpm for 5 minutes to ensure that the composite microparticles are evenly dispersed in the hair wax base.
[0086] S4. Cool the system to 55°C, add 0.4 parts tocopherol and 0.2 parts fragrance, stir at 500 rpm for 5 minutes to mix evenly; continue to cool to 50°C, fill the wax while it is still fluid, let it cool naturally to room temperature, and then let it stand at 25°C for 48 hours to obtain an easy-to-wash styling wax.
[0087] Comparative Example 1
[0088] The difference from Example 1 is that no composite microparticles are added, while the other raw materials, the amount of raw materials used, and the preparation method of the hair wax are the same as in Example 1.
[0089] Comparative Example 2
[0090] The difference from Example 1 is that 3 parts of untreated sodium polyacrylate grafted starch are used instead of 3 parts of composite microparticles. That is, 3 parts of sodium polyacrylate grafted starch are directly added to the hair wax base in step S3. The other raw materials, raw material amounts and preparation methods of hair wax are the same as in Example 1.
[0091] Comparative Example 3
[0092] The difference from Example 1 is that: instead of pre-preparing composite microparticles, each component constituting the three parts of composite microparticles is added separately to the hair wax system; wherein, according to the mass ratio of each component of the composite microparticles in Example 1, 2.64 parts of sodium polyacrylate grafted starch, 0.15 parts of PEG-100 stearate, 0.15 parts of glyceryl stearate and 0.06 parts of microcrystalline wax are used respectively; the 0.06 parts of microcrystalline wax are added in step S1, the 0.15 parts of PEG-100 stearate and 0.15 parts of glyceryl stearate are added in step S2, and the 2.64 parts of sodium polyacrylate grafted starch are added in step S3. The remaining raw materials, raw material amounts and the preparation method of the styling hair wax are the same as in Example 1.
[0093] Comparative Example 4
[0094] The difference from Example 1 is that PEG-100 stearate is not added to the composite microparticles. The composite microparticles are prepared from 93 parts of sodium polyacrylate grafted starch, 5 parts of glyceryl stearate and 2 parts of microcrystalline wax. Apart from the above differences, the preparation method of the composite microparticles and the other raw materials, raw material amounts and preparation methods of the hair styling wax are the same as those in Example 1.
[0095] Comparative Example 5
[0096] The difference from Example 1 is that no glycerol stearate is added to the composite microparticles. The composite microparticles are prepared from 93 parts of sodium polyacrylate grafted starch, 5 parts of PEG-100 stearate and 2 parts of microcrystalline wax. Apart from the above differences, the preparation method of the composite microparticles and the other raw materials, raw material amounts and preparation methods of the hair styling wax are the same as those in Example 1.
[0097] Comparative Example 6
[0098] The difference from Example 1 is that no microcrystalline wax is added to the composite microparticles. The composite microparticles are prepared from 90 parts of sodium polyacrylate grafted starch, 5 parts of PEG-100 stearate and 5 parts of glyceryl stearate. Apart from the above differences, the preparation method of the composite microparticles and the other raw materials, raw material amounts and preparation methods of the hair styling wax are the same as those in Example 1.
[0099] Test 1: Settling Performance Test
[0100] Test subjects: blank hair strands, Examples 1-3 and Comparative Examples 1-6. Among them, the blank hair strands were artificially synthesized standard hair strands of the same specifications as those in the Examples and Comparative Examples. After the same pre-washing, drying and constant temperature and humidity balancing treatment, no hair wax was applied, and the strands were placed horizontally for 12 hours under the conditions of 25±1℃ and 60±2% relative humidity before the bending force test was performed directly.
[0101] Test method: Take a synthetic standard hair bundle with a length of 15cm, a width of 2cm, and a weight of 3.0±0.1g. First, clean the hair bundle with a 5% sodium lauryl ether sulfate aqueous solution, then rinse it with 40℃ warm water, let it air dry, and then place it in a constant temperature and humidity chamber at 25±1℃ and 60±2% relative humidity for 24 hours for later use. Then, weigh 0.05g of each hair wax sample to be tested, apply it evenly to the surface of the hair bundle, and comb it 10 times from the root to the tip with a standard fine-tooth comb to ensure that the hair wax is evenly distributed on the hair bundle. The hair strands coated with hair wax were then placed in a constant temperature and humidity chamber at 25±1℃ and 60±2% relative humidity for 12 hours to allow the hair wax setting layer to fully stabilize. Next, the treated hair strands were fixed to the fixture of a bending force tester. The pressure head was set to descend at a speed of 50 mm / min and a descent distance of 30 mm. The maximum peak force observed during the bending process was recorded and taken as the bending force of the hair strand, expressed in grams per force (gf). Five parallel hair strand samples were used in each group, and each strand was tested once. The average value of the five parallel sample test results was taken as the bending force of that group. A higher bending force indicates stronger styling support provided by the hair wax.
[0102] The test data for Test 1 is shown in Table 1.
[0103] Table 1
[0104]
[0105] As shown in Table 1, the bending force of the unbonded hair strand was 2.3 gf, while the bending forces of Examples 1-3 were 9.2 gf, 8.6 gf, and 9.5 gf, respectively. This indicates that the styling wax obtained by the present invention can significantly improve the bending support capacity of the hair strand. The bending forces of Comparative Examples 1-6 were 8.5-8.9 gf, which are generally similar to those of Examples 1-3, with Comparative Example 1 without the addition of composite microparticles having a bending force of 8.8 gf. This indicates that the styling support performance of the hair wax of the present invention is mainly provided by the oil-wax structure formed by microcrystalline wax, candelilla wax, and ceresin wax. The introduction of composite microparticles and the change in the composition of composite microparticles did not significantly weaken the basic styling performance of the hair wax, indicating that the improvement in washing performance by the present invention does not come at the expense of reduced styling ability.
[0106] Test 2: Cleaning and Removal Performance Test
[0107] Test subjects: Examples 1-3 and Comparative Examples 1-6.
[0108] Test Method: Take a synthetic standard hair bundle of the same specifications as Test 1, wash it with a 5% sodium lauryl ether sulfate aqueous solution, rinse it with 40℃ warm water, air dry it naturally, and then place it in a constant temperature and humidity chamber for equilibration at 25±1℃ and 60±2% relative humidity for 24 hours. Weigh and record the initial mass m0 of the hair bundle using an analytical balance with a sensitivity of 0.1mg. Then, weigh 0.05g of each hair wax sample to be tested, apply it evenly to the surface of the corresponding hair bundle, and comb it 10 times from the root to the tip using a standard fine-tooth comb to ensure even distribution of the hair wax. Subsequently, place the hair bundle horizontally in a constant temperature and humidity chamber for 12 hours at 25±1℃ and 60±2% relative humidity, and weigh and record the mass m1 of the hair bundle after applying the hair wax using the same analytical balance. Adjust the water temperature in the constant temperature water bath to 40±1℃. Take a 1000mL beaker, add 500mL of water at 40±1℃, and then add 5.0g of standard shampoo. The standard shampoo is sodium lauryl ether sulfate-based shampoo with a surfactant content of 10%, thus making the surfactant concentration in the resulting washing solution approximately 0.1%. Stir to evenly disperse the standard shampoo in the water. Completely immerse the hair bundle coated with hair wax in the washing solution and wash using a constant stirring speed of 100rpm for 2min. After washing, remove the hair bundle and rinse it in flowing warm water at 40±1℃ for 2min, with the water flow rate controlled at approximately 2L / min. Allow the rinsed hair bundle to air dry naturally, then place it in a constant temperature and humidity chamber and equilibrate for 24h at 25±1℃ and 60±2% relative humidity. Weigh and record the mass (m2) of the washed hair bundle using the analytical balance. The residual rate and removal rate after washing are calculated using the following formulas: Residual rate after washing (%) = [(m2-m0) / (m1-m0)] × 100%; Removal rate after washing (%) = [(m1-m2) / (m1-m0)] × 100%. Where: m0 is the mass of the hair bundle before applying hair wax; m1 is the mass of the hair bundle after applying hair wax and equilibrating at constant temperature and humidity; m2 is the mass of the hair bundle after washing, drying, and equilibrating at constant temperature and humidity again. Five independent parallel hair bundles are set up for each group, and each hair bundle undergoes one complete test independently. The average value of the five parallel sample test results is taken as the test result for that group of samples. A higher removal rate and a lower residual rate after washing indicate better removal performance of the hair wax in a single standard washing process.
[0109] The test data for Test 2 is shown in Table 2.
[0110] Table 2
[0111]
[0112] As shown in Table 2, the removal rates of the first wash in Examples 1-3 were 93.8%, 93.2%, and 94.3%, respectively, with residual rates below 7% after washing. In contrast, Comparative Example 1, without the addition of composite microparticles, had a removal rate of only 62.2%, indicating that the introduction of composite microparticles significantly promoted the removal of oil-wax residue. Comparative Example 2 used untreated sodium polyacrylate grafted starch directly instead of composite microparticles, achieving a removal rate of 75.2%, demonstrating that the water absorption of sodium polyacrylate grafted starch improved the washing performance to some extent, but was still significantly lower than the effect of intact composite microparticles. Comparative Example 3 used the same raw materials as Example 1 but without pre-composite treatment, achieving a removal rate of 82.3%, indicating that the washing effect of this invention is not solely due to the simple coexistence of the raw materials in hair wax; pre-construction of composite microparticles plays a crucial role in improving washing performance. The cleaning and removal rates of Comparative Examples 4-6 were 80.8%, 79.8%, and 83.9%, respectively, which were all lower than those of Example 1. This indicates that the combination of PEG-100 stearate, glyceryl stearate, and microcrystalline wax with sodium polyacrylate grafted starch is beneficial to obtaining a better overall cleaning effect.
[0113] Test 3: Dry-state combing performance test after washing
[0114] Test subjects: blank hair bundles, Examples 1-3, and Comparative Examples 1-6. The blank hair bundles were synthetic standard hair bundles of the same specifications as those in the Examples and Comparative Examples, without any hair wax applied, and treated under the same washing, rinsing, air-drying, and constant temperature and humidity equilibration conditions as in Test 2. Examples 1-3 and Comparative Examples 1-6 were tested using hair bundles that had undergone the washing, rinsing, air-drying, and constant temperature and humidity equilibration conditions described in Test 2.
[0115] Test Method: The hair bundle to be tested is fixed on the hair bundle clamp of the combing force tester, keeping the hair bundle in a vertical hanging state. A standard fine-tooth comb is fixed on the moving arm of the instrument, so that the comb teeth pass vertically through the hair bundle. The comb tooth moving speed is set to 500 mm / min, and a single combing is performed from the root of the hair bundle to the tip, with a combing distance of 10 cm. The maximum combing force during the comb teeth passing through the hair bundle is recorded, in grams per force (gf). Five independent parallel hair bundles are set up in each group, and each hair bundle is subjected to only one formal combing test. The average of the maximum combing force of the five parallel samples is taken as the maximum combing force F of the sample group. The maximum combing force increase rate is calculated according to the following formula: Maximum combing force increase rate (%) = [(F sample - F blank) / F blank] × 100%. Where: F sample is the average maximum combing force of the hair bundle after washing in the example or comparative example; F blank is the average maximum combing force of the blank hair bundle. The lower the increase rate of maximum combing force, the better the dry combing performance of the hair strands after washing with hair wax, and it can indirectly reflect that the influence of oil and wax residue on the hair surface on combing performance is smaller.
[0116] The test data for Test 3 is shown in Table 3.
[0117] Table 3
[0118]
[0119] As shown in Table 3, the maximum combing force of the unprocessed hair strand was 8.2 gf. The maximum combing force of Examples 1-3 after washing was 9.5-10.3 gf, corresponding to an increase in maximum combing force of only 15.9%-25.6%, which is relatively close to that of the unprocessed hair strand. In contrast, the maximum combing force of Comparative Example 1 reached 16.7 gf, with an increase in maximum combing force of 103.7%. The increase in maximum combing force of Comparative Examples 2-6 also reached 40.2%-64.6%, all significantly higher than the Examples. This result corresponds well with the washing removal rate in Table 2, that is, the examples with higher washing removal rates have lower combing resistance after washing, indicating that there is less oily and waxy styling material remaining on the hair surface. At the same time, the test results of Comparative Examples 2-6 further show that the surface composite treatment of sodium polyacrylate grafted starch and the coordination between the components of the composite microparticles are beneficial to reducing post-wash residue and improving the dry combing performance of the hair strand.
[0120] In summary, this invention pre-constructs composite microparticles from sodium polyacrylate grafted starch, PEG-100 stearate, glyceryl stearate, and microcrystalline wax, and disperses them in an oil-based hair wax matrix. While maintaining the basic styling and support properties of the hair wax, it can significantly improve the removal rate in a single wash and reduce the combing resistance of the hair strands after washing. Compared with systems that do not contain composite microparticles, directly add untreated sodium polyacrylate grafted starch, or whose components are not pre-composite, this invention exhibits superior overall cleaning performance. This indicates that the pre-construction of composite microparticles and the synergy between their components can effectively promote the removal of oil-based styling residue from the hair surface, thereby achieving a balance between styling performance and easy washing.
[0121] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. An easy-to-wash styling wax, characterized in that, The ingredients include the following: microcrystalline wax, candelilla wax, ceresin wax, hydrogenated polyisobutylene, C12-15 benzoyl alcohol, caprylic / capric triglyceride, composite microparticles, PEG-40 hydrogenated castor oil, polyglycerol-10 laurate, and structure modifiers. The composite microparticles are composed of sodium polyacrylate grafted starch, PEG-100 stearate, glyceryl stearate and microcrystalline wax, wherein the PEG-100 stearate, glyceryl stearate and microcrystalline wax are loaded on the surface of the sodium polyacrylate grafted starch particles.
2. The easy-to-wash styling wax according to claim 1, characterized in that, The mass ratio of sodium polyacrylate grafted starch, PEG-100 stearate, glyceryl stearate and microcrystalline wax in the composite microparticles is (85-90):(4-6):(4-6):(1-3).
3. The easy-to-wash styling wax according to claim 2, characterized in that, The average particle size of the sodium polyacrylate grafted starch is 10-30 μm.
4. The easy-to-wash styling wax according to claim 2, characterized in that, The method for preparing the composite microparticles is as follows: PEG-100 stearate, glyceryl stearate and microcrystalline wax are mixed and heated to form a melt. The resulting melt is added to sodium polyacrylate grafted starch and mixed to make the melt adhere to the surface of the sodium polyacrylate grafted starch particles. Then, the particles are cooled, solidified, depolymerized and sieved to obtain the composite microparticles.
5. The easy-to-wash styling wax according to claim 4, characterized in that, The screening step is as follows: screening is performed using a sieve with a mesh size of 50-75μm.
6. The easy-to-wash styling wax according to claim 1, characterized in that, The raw materials include the following parts by weight: 12-16 parts microcrystalline wax, 5-7 parts candelilla wax, 4-6 parts ceresin wax, 31-36 parts hydrogenated polyisobutylene, 16-20 parts C12-15 benzoyl alcohol ester, 10-13 parts caprylic / capric triglyceride, 2.5-3.5 parts composite microparticles, 3.5-4.5 parts PEG-40 hydrogenated castor oil, 1.5-2.5 parts polyglycerol-10 laurate, and 1.0-2.0 parts structure modifier.
7. The easy-to-wash styling wax according to claim 1 or 6, characterized in that, The structure modifier is hydrophobic fumed silica.
8. The easy-to-wash styling wax according to claim 6, characterized in that, It also includes the following raw materials in parts by weight: 0.2-0.4 parts tocopherol and 0-0.3 parts fragrance.
9. A method for preparing an easy-to-wash styling wax according to any one of claims 1-8, characterized in that, Includes the following steps: S1. Mix microcrystalline wax, candelilla wax, ceresin, hydrogenated polyisobutylene, C12-15 alcohol benzoate and caprylic / capric triglyceride and heat to 80-85℃ to melt the wax components and obtain the oil wax matrix. S2. Add PEG-40 hydrogenated castor oil and polyglycerol-10 laurate to the oil and wax matrix, mix evenly, then add a structure modifier and disperse evenly to obtain the hair wax matrix; S3. After cooling the hair wax base to 60-65℃, add the composite microparticles and stir to make the composite microparticles evenly dispersed in the hair wax base; S4. Fill at 45-50℃, cool and solidify, and let stand to obtain the easy-to-clean hair wax.
10. The method for preparing an easy-to-wash styling wax according to claim 9, characterized in that, In step S1, the heating and melting temperature of microcrystalline wax, candelilla wax, and ceresin wax is 80-85℃, and the stirring time is 15-20 minutes; in step S3, after cooling to 60-65℃, composite microparticles are added, and the stirring time is 5-10 minutes.
